Uma análise da receita tributária do estado do Amazonas no período de 2015 - 2022: a contribuição do ICMS para a arrecadação tributária amazonense no período analisado - Souza, Luana Penha de (Brasil, 2024)
Tax collection is a fundamental aspect of the financial management of any region, playing a crucial role in financing government activities and providing public services to the population. In the context of the state of Amazonas, tax collection is influenced by a variety of factors, with the ICMS (Tax on Circulation of Goods and Services) being one of the main sources of revenue. This research work seeks to examine the contribution of ICMS to tax collection in the state of Amazonas, investigating the contribution of the ICMS proportion to such collection and describes the variations that such effects caused in tax collection. To offer theoretical support, a theoretical foundation was carried out and a brief literature review showing concepts and different perspectives on the given subject. The method of this study had a descriptive and explanatory approach, in which these approaches continued the quantitative part of the study, that is, it is a methodology that forms the basis for drawing general conclusions from the research and predicting the results. As a result, it was noted that ICMS has an average contribution of 88.86% of the general total of tax collections, that is, more than half of these collections over the periods analyzed.